In silico Analyses of Subtype Specific HIV-1 Tat-TAR RNA Interaction Reveals the Structural Determinants for Viral Activity - Ronsard, Larance; Rai, Tripti; Rai, Devesh; Ramachandran, Vishnampettai G.; Banerjea, Akhil C. (Frontiers in Microbiology, 2017)
HIV-1 Tat transactivates viral genes through strong interaction with TAR RNA. The stem-loop bulged region of TAR consisting of three nucleotides at the position 23 to 25 and the loop region consisting of six nucleotides at the position 30 to 35 are essential for viral transactivation. The arginine motif of Tat (five arginine residues on subtype TatC) is critically important for TAR interaction. Any mutations in this motif could lead to reduce transactivation ability and pathogenesis. Here, we identified structurally important residues (arginine and lysine residues) of Tat in this motif could bind to TAR via hydrogen bond interactions which is critical for transactivation. Natural mutant Ser46Phe in the core motif could likely led to conformational change resulting in more hydrogen bond interactions than the wild type Tat making it highly potent transactivator. Importantly, we report the possible probabilities of number of hydrogen bond interactions in the wild type Tat and the mutants with TAR complexes. This study revealed the differential transactivation of subtype B and C Tat could likely be due to the varying number of hydrogen bonds with TAR. Our data support that the N-terminal and the C-terminal domains of Tat is involved in the TAR interactions through hydrogen bonds which is important for transactivation. This study highlights the evolving pattern of structurally important determinants of Tat in the arginine motif for viral transactivation.